2015
DOI: 10.1590/1678-457x.6655
|View full text |Cite
|
Sign up to set email alerts
|

Extraction, purification and characterization of inhibitor of trypsin from Chenopodium quinoa seeds

Abstract: A novel trypsin inhibitor of protease (CqTI) was purified from Chenopodium quinoa seeds. The optimal extracting solvent was 0.1M NaCl pH 6.8 (p < 0.05). The extraction time of 5h and 90 °C was optimum for the recovery of the trypsin inhibitor from C. quinoa seeds. The purification occurred in gel-filtration and reverse phase chromatography. CqTI presented active against commercial bovine trypsin and chymotrypsin and had a specific activity of 5,033.00 (TIU/mg), which was purified to 333.5-fold. The extent of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 38 publications
(53 reference statements)
1
11
0
1
Order By: Relevance
“…The lyophilized was dissolved in 10 mmol/L Tris-HCl, pH 8.0 and protein concentration was determined using Coomassie blue staining by Bradford method [36]. The albumin composition was analyzed by Tricine Sodium Dodecyl Sulfate Polyacrylamide Gel (SDS-PAGE) according to the procedure of Schägger and von Jagow [37] with some modifications [38]. The albumin ‘solutions were mixed with a sample buffer (0.05M Tris-HCl at pH 6.8, 4% ( w / v ) SDS, 12% ( v / v ) glycerol, 0.01% ( w / v ) bromophenol blue, and 2% ( v / v ) 2-ME) and heated for 3 min in a boiling water bath, then centrifuged at 10,000 rpm for 3min.…”
Section: Methodsmentioning
confidence: 99%
“…The lyophilized was dissolved in 10 mmol/L Tris-HCl, pH 8.0 and protein concentration was determined using Coomassie blue staining by Bradford method [36]. The albumin composition was analyzed by Tricine Sodium Dodecyl Sulfate Polyacrylamide Gel (SDS-PAGE) according to the procedure of Schägger and von Jagow [37] with some modifications [38]. The albumin ‘solutions were mixed with a sample buffer (0.05M Tris-HCl at pH 6.8, 4% ( w / v ) SDS, 12% ( v / v ) glycerol, 0.01% ( w / v ) bromophenol blue, and 2% ( v / v ) 2-ME) and heated for 3 min in a boiling water bath, then centrifuged at 10,000 rpm for 3min.…”
Section: Methodsmentioning
confidence: 99%
“…This is consistent with the observations by Nicholls, Sharp, and Honig [34], who found that the conformation of trypsin inhibitors from soybean was changed due to the effect of n-propanol. Others have also reported on the use of organic solvents to deactivate trypsin inhibitors in soybeans [35][36][37]. Furthermore, a more hydrophobic solvent, dichloromethane/methanol (1:1), was not suitable for the extraction of the two known trypsin inhibitors in Gac seeds, MCoTI-I, and MCoTI-II [14].…”
Section: Effect Of Extraction Methods On the Trypsin Inhibitor Yieldmentioning
confidence: 99%
“…They generally have a higher molecular weight than other AFPs and contain a unique disulfide‐linked, nine‐residue loop. Among these PIs, the most studied are soybean trypsin inhibitors (Kunitz) and soybean proteinase inhibitors ( Bowman‐Birk, BBI ) (Kim et al., ; Pesoti et al., ). BBIs are cysteine‐rich proteins of 1.5 to 20 kDa, with up to seven disulfide bonds, that possess inhibitory activities against proteases (Fernandez et al., ).…”
Section: Plant Sources Of Afpsmentioning
confidence: 99%